HOSPITALIZATION AND AMBULATORY TREATMENT OF CHILDREN: ADVANTAGES AND RISKS - M.D. Bakradze ("Paediatrician" Publishers LLC, 2009)
The need in hospitalization of pediatric patients was significantly decreased in last 20 years due to including of innovative methods of treatment into the practice. This fact leaded to arising of questions, related to ambulatory treatment. The article presents analysis of advantages and shortcomings of present being practice of children's with acute diseases management at ambulatory and hospital stages. It was shown that the number of beds (calculated to 10 000 children under the age 0-14 years old) is differ from 4-5 in USA to 90 in Russian Federation, with tendency to beds' concentration in large hospitals. The main reason of hospitalization is nosocomial respiratory (up to 40% of cases) and rotaviral (up to 25% of cases in epidemic season) infections. It was marker, that shortening of stay in hospital and implementation of hospital-replacing technologies (day hospital) for the treatment of children with chronic pathology can decrease the rate of morbidity with nosocomial infections. Lessening the need in hospital stay can be realized by optimization of ambulatory care, particularly, shortening of patient's visits at home, and using diagnostic abilities of out-patient clinics for the needs of patients with acute diseases. Key words: children, hospitalization, ambulatory treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):26-31)